2017
DOI: 10.1002/mus.25554
|View full text |Cite
|
Sign up to set email alerts
|

Decreased intracellular [Ca2+] coincides with reduced expression of Dhprα1s, RyR1, and diaphragmatic dysfunction in a rat model of sepsis

Abstract: Decreased intracellular [Ca ] coincides with diaphragmatic contractility and decreased expression of DHPRα1s and RyR1 in sepsis. Muscle Nerve 56: 1128-1136, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Sepsis-induced diaphragmatic dysfunction includes the two aspects of decreased diaphragm contractility and diaphragm atrophy 2 . We found that contractile dysfunction was earlier than diaphragmatic atrophy in septic patients of our study, which had confirmed by basic and clinical studies 16 , 27 . With the aggravation of infection severity, we found a further decrease in the diaphragmatic contractile function by ultrasound, including parameters of TF, E QB /E DB, velocity in deep breathing and AUDMC.…”
Section: Discussionsupporting
confidence: 88%
“…Sepsis-induced diaphragmatic dysfunction includes the two aspects of decreased diaphragm contractility and diaphragm atrophy 2 . We found that contractile dysfunction was earlier than diaphragmatic atrophy in septic patients of our study, which had confirmed by basic and clinical studies 16 , 27 . With the aggravation of infection severity, we found a further decrease in the diaphragmatic contractile function by ultrasound, including parameters of TF, E QB /E DB, velocity in deep breathing and AUDMC.…”
Section: Discussionsupporting
confidence: 88%